Complications of Acute Meningoencephalitis among Children Admitted to Al-Wahda Teaching Hospital in Aden, Yemen - Iman Mokammed Bawazeer (Yemeni Journal for Medical Sciences, 2019)
Objective: To determine the types and frequencies of complications associated with acute meningoencephalitis (ME) among children admitted  to hospitals in Aden, Yemen.